Sosialisasi dan Pendampingan Perpajakan Untuk Meningkatkan Kesadaran Wajib Pajak Kota Bengkulu - Rina Yuniarti; Ahmad Junaidi; Budi Astuti; Pedi Riswandi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Tax is a mandatory community contribution that is forced without getting reciprocal services to pay general expenses and investment capital for the independence of the state. The problems experienced by employees and lecturers at the University of Muhammadiyah Bengkulu and the University of Prof Dr. Hazairin, SH Bengkulu are that they do not have an NPWP and do not understand how to report taxes online via e- filing. This activity was attended by approximately 25 participants who are employees and lecturers. The results of lecturer and employee activities have increased by 50% who have an NPWP and 70% understand reporting taxes online via e-filling compared to before the service was carried out. Thus, the hope of the services team is that it will increase taxpayers who have an NPWP and report their taxes every year